2016
DOI: 10.1007/s12011-016-0912-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Apoptosis Triggered by Sub-Chronic Lead Exposure in Mice Spleen: a Histopathological Study

Abstract: Lead (Pb) is an environmental oncogenic metal that induces immunotoxicity and anaemia. Emerging evidence has linked Pb toxicity with endoplasmic reticulum-driven apoptosis and autophagy. Glucose-regulated protein of 78 kDa (Grp78 or binding immunoglobulin protein (BiP)), a master endoplasmic reticulum chaperone, drives macrophage activation and regulates protein folding and calcium flux in response to heavy metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 65 publications
1
20
0
1
Order By: Relevance
“…This distribution of reactive microglia is analogous with previously published data on their band-like accumulation in regions surrounding the ischemic core during the first week of ischemic stroke ( Li et al, 2013 , 2014 ), indicating that instead of containing pre-existing microglia, the lesion core was progressively infiltrated by microglia migrating from the peri-lesional area. These activated microglia/macrophages showed intense immunoreactivity for GRP78, as previously reported ( Fan et al, 2015 ; Yang et al, 2015 ; Corsetti et al, 2017 ; Jin et al, 2018a ). Thus, the temporal patterns of vascular GRP78 appeared to overlap with the period during which GRP78 was expressed by microglia/macrophages recruited into the lesion core.…”
Section: Discussionsupporting
confidence: 87%
“…This distribution of reactive microglia is analogous with previously published data on their band-like accumulation in regions surrounding the ischemic core during the first week of ischemic stroke ( Li et al, 2013 , 2014 ), indicating that instead of containing pre-existing microglia, the lesion core was progressively infiltrated by microglia migrating from the peri-lesional area. These activated microglia/macrophages showed intense immunoreactivity for GRP78, as previously reported ( Fan et al, 2015 ; Yang et al, 2015 ; Corsetti et al, 2017 ; Jin et al, 2018a ). Thus, the temporal patterns of vascular GRP78 appeared to overlap with the period during which GRP78 was expressed by microglia/macrophages recruited into the lesion core.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, molecular analysis, although much more sensitive in highlighting proteins and very often used exclusively, does require immediate freezing and homogenization of the sample. As a consequence, it does not take into account the specificities of protein location, such as tissue morphology and organization [94]. This is a major limitation in the exclusive use of molecular analysis, which we believe is comparable if not superior to IHC.…”
Section: Study Limitationsmentioning
confidence: 97%
“…In a similar study, Aldahmash et al [32] reported lead intake to cause severe alterations in the kidney and spleen, which was manifested by hepatocytes degeneration, leukocytic infiltration, ill-defined architecture of the spleen, presence of large macrophages and lymphoid necrosis. Hypocellular white pulp, enlargement of venous sinusoids, clustering of heterochromatin in the nucleus, vacuolation in the cytoplasm, swelling of mitochondria and complete distortion of rough endoplasmic reticulum cisterns are also some of the effects of lead [33,34].…”
Section: Resultsmentioning
confidence: 99%